PENERAPAN MODEL JIGSAW DENGAN MEDIA GAMBAR DALAM PENINGKATAN PEMBELAJARAN IPS TENTANG MASALAH SOSIAL PADA SISWA KELAS IV SDN MUJUR 01 TAHUN AJARAN 2015/2016 - Utami, Khikmah Laelatul; Suhartono, Suhartono; Salimi, Moh (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract. The Application of Jigsaw Model Using Pictures Media in Improving Social Science Learning about Social Problems for the Fifth Grade Students of SDN Mujur 01 in the Academic Year of 2015/2016. The objectives of this research are to describe the application of Jigsaw model using picture media and to improve social science learning. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Subjects of the research were fourth grade students of SDN Mujur 01. Data were analyzed using data reduction, data display, and drawing conclusion or verification. The results of this research showed that: (1) there are 10 steps of the application of Jigsaw model using picture media, namely: (a) group division in the beginning, (b) giving assignment, (c) new group division, (d) discussion of new groups, (e) new group back to previous group, (f) group presentation, (g) presentation in the classroom, (h) discussion, (i) evaluation, and (j) closing. Furthermore, the application of Jigsaw model using picture media improve social science learning. It was proven by the increase of the completeness of students learning outcomes in the first cycle 54.3%, in the second cycle 81.4%, and in the third cycle 91.4%. Keywords: Jigsaw, pictures media, learning, social science Abstrak. Penerapan Model Jigsaw dengan Media Gambar dalam Peningkatan Pembelajaran IPS tentang Masalah Sosial pada Siswa Kelas IV SDN Mujur 01 Tahun Ajaran 2015/2016. Penelitian ini bertujuan untuk mendeskripsikan penerapan model jigsaw dengan media gambar dan meningkatkan pembelajaran IPS. Penelitian ini merupakan penelitian tindakan kelas (PTK) kolaborasi. Subjek penelitian ini adalah siswa kelas IV SDN Mujur 01. Teknik analisis data dengan langkah, yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa penggunaan model jigsaw dengan media gambar dilakukan melalui sepuluh langkah, yaitu (a) pembentukan kelompok awal; (b) pembagian tugas; (c) pembentukan kelompok baru; (d) diskusi kelompok baru; (e) kelompok baru kembali ke kelompok awal; (f) presentasi kelompok; (g) presentasi kelas; (h) pembahasan; (i) evaluasi; dan (j) penutup; serta dapat meningkatkan pembelajaran IPS yang dibuktikan dengan adanya peningkatan ketuntasan hasil belajar siswa, yaitu siklus I 54,3%, siklus II 81,4%, dan siklus III 91,4%. Kata kunci: jigsaw, media gambar, pembelajaran, IPS